The Role of Leadership and Workplace Climate in Promoting Employee Well-Being and Engagement - Adiawaty, Susi; Moeins, Anoesyirwan (Yayasan Sinergi Kawula Muda, 2024)
The impact of working conditions on employee mental health and organizational commitment has gained increasing attention in occupational health research. This study examines how job stress, burnout, and workplace support influence employee well-being and retention. Using a narrative review approach, literature was sourced from databases such as PubMed, Scopus, Google Scholar, and PsycINFO to ensure comprehensive coverage of recent empirical findings. The results highlight the detrimental effects of high job stress and burnout on employee satisfaction and commitment, particularly in the healthcare sector. Organizational support and a positive psychosocial climate are identified as essential factors in mitigating workplace stress and enhancing job retention. Comparative analysis across regions reveals significant variations in how employees experience and respond to job stress, influenced by workplace culture and managerial practices. Systemic interventions, including leadership development, psychological support mechanisms, and work-life balance policies, have demonstrated efficacy in reducing burnout and improving organizational commitment. These findings underscore the necessity for organizations to implement evidence-based strategies that enhance employee well-being. The study concludes that addressing workplace mental health requires a comprehensive approach that incorporates managerial, systemic, and policy-level interventions. Future research should focus on long-term organizational reforms and the integration of emerging technologies in stress management to foster sustainable workforce engagement.